Underlying profits and financial reporting quality in Australia. (11th May 2022) - Yang, Yiru; Abeysekera, Indra
This study examines Australian Securities Exchange (ASX) 200 listed firms that reported underlying profits from years 2009 to 2012 to determine whether the underlying profits reflect accounting-based and market-based financial reporting quality. The panel-data modelling results show that there is no relationship between underlying profits and financial reporting quality. The study finds that underlying profits are positively related to earnings management, suggesting that firms engaging in opportunistic accrual management aggressively report underlying profits. The study contributes to the debates about utility of underlying profits, by empirically informing that underlying profits do not contain value-relevant information for investor decision-making.